Critical success factors of the nine challenges in Malaysia's Vision 2020 - Islam, Rafikul (Elsvier, 2010)
By the year 2020, Malaysia aspires to become a fully developed nation. In order to realize this vision, formally termed ‘Vision 2020’, Malaysia must address nine strategic challenges identified by the government of former Prime Minister Tun Dr. Mahathir bin Mohamad. These challenges are: (1) Establishing a united Malaysian nation, (2) Creating a psychologically liberated, secure, and developed Malaysian society, (3) Developing a mature democratic society, (4) Forming a community that has high morale, ethics, and religious strength, (5) Establishing a mature, liberal and tolerant society, (6) Establishing a scientific and progressive society, (7) Establishing a fully caring society, (8) Ensuring an economically just society, and (9) Establishing a prosperous society. The present paper seeks to identify and rank the critical success factors of these nine challenges by applying the Analytic Hierarchy Process. A number of ‘front-line’ critical success factors are discussed at length. The paper also analyzes the impact of respondents’ demography on the outcomes. The findings are expected to provide valuable guidelines to the Malaysian government in course of developing effective action plans to achieve Vision 2020.